2017
DOI: 10.1126/scitranslmed.aaf9655
|View full text |Cite
|
Sign up to set email alerts
|

IgA-coated E. coli enriched in Crohn’s disease spondyloarthritis promote T H 17-dependent inflammation

Abstract: Peripheral spondyloarthritis (SpA) is a common extra-intestinal manifestation in patients with active inflammatory bowel disease (IBD) characterized by inflammatory enthesitis, dactylitis, or synovitis of non-axial joints. However, a mechanistic understanding of the link between intestinal inflammation and SpA has yet to emerge. Here, we evaluated and functionally characterized the fecal microbiome of IBD patients with or without peripheral SpA. Coupling the sorting of IgA-coated microbiota with 16S rRNA-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
248
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(269 citation statements)
references
References 67 publications
(113 reference statements)
12
248
1
1
Order By: Relevance
“…Alterations in the composition of the intestinal microbiome have been shown to impact mucosal T cell effector function in mouse models (15, 16). To evaluate the impact of two donor FMP on mucosal immunity in active UC, we profiled mucosal CD4+ T cell function in rectal biopsies performed at the time of FMT and 4 weeks post-FMT (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in the composition of the intestinal microbiome have been shown to impact mucosal T cell effector function in mouse models (15, 16). To evaluate the impact of two donor FMP on mucosal immunity in active UC, we profiled mucosal CD4+ T cell function in rectal biopsies performed at the time of FMT and 4 weeks post-FMT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although Crohn’s disease was initially characterized as a Th1- and UC as a Th2-driven inflammatory disease, additional T cell subsets have been identified to play a role in IBD mucosal barrier immunity including regulatory T cells and IL-23 responsive Th17 cells (15). In mouse models, human microbiota have been shown to play a critical role in regulating Th1 (19), regulatory T cells (20), and Th17 (16, 21). Immune cell analyses in FMT studies have been limited, but a recent analysis in Crohn’s disease revealed a borderline increase in CD25+ CD127 lo CD4+ T cells at 12 weeks post-FMT (17).…”
Section: Discussionmentioning
confidence: 99%
“…Viladomiu et al revealed that AIEC isolated from patients with CD with spondyloarthritis induce Th17 mucosal immunity in germ-free mice, as well as specific pathogen-free mice, compared with non-AIEC strains. This demonstrates that AIEC can induce Th17 polarisation, even in the presence of other commensal microbiota, which requires the virulence-associated metabolic enzyme propanediol dehydratase 135. Recently, it has been shown that infection with the LF82 strain could induce the release of exosomes, which activate NF-κB, mitogen-activated protein kinases p38 and c-Jun N-terminal kinase, as well as increase the secretion of proinflammatory cytokines in vitro and in vivo.…”
Section: Aiec and The Gut Immune Systemmentioning
confidence: 96%
“…Fecal IgA varies independently of bacterial phylogeny and can be perturbed during disease 30 . Enrichment of Enterobacteriaceae and Lachnospiraceae in IgA-coated and IgA-negative microbiota, respectively, in both Crohn’s disease–associated spondyloarthritis 31 and malnutrition 26 , suggest that a potential core IgA response may exist in various inflammatory conditions.…”
Section: Toward Identification Of An Immune-modulatory Microbiotamentioning
confidence: 99%